2020
DOI: 10.1186/s12889-020-09429-3
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of the COVID-19 pandemic on physical activity and sedentary behavior in children living in the U.S.

Abstract: Background: COVID-19 restrictions such as the closure of schools and parks, and the cancellation of youth sports and activity classes around the United States may prevent children from achieving recommended levels of physical activity (PA). This study examined the effects of the COVID-19 pandemic on PA and sedentary behavior (SB) in U.S. children. Method: Parents and legal guardians of U.S. children (ages 5-13) were recruited through convenience sampling and completed an online survey between April 25-May 16, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

78
790
9
45

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 789 publications
(922 citation statements)
references
References 34 publications
78
790
9
45
Order By: Relevance
“…The small changes in PA were surprising and contrary to ndings that have reported large declines in PA during the pandemic period among older children 9,15,16 . These differences may be explained methodologically.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The small changes in PA were surprising and contrary to ndings that have reported large declines in PA during the pandemic period among older children 9,15,16 . These differences may be explained methodologically.…”
Section: Discussioncontrasting
confidence: 99%
“…Children spent less time outdoors on weekdays and weekend days during the pandemic. This is consistent with other studies of children and youth during the pandemic 9,15 . Time spent outdoors provides many bene ts for children and their parents including higher levels of PA 19 ; indeed, in those countries where children were able to play outdoors, higher levels of PA were reported.…”
Section: Discussionsupporting
confidence: 93%
“…Previously published studies are in line with our findings, which found that children had different patterns of activity than what was seen before COVID-19. For example, changes in physical activity and sedentary behavior were reported by parents and legal guardians of children living in the U.S. using an online survey [ 2 ]. Among Spanish youth, the lockdown substantially reduced physical activity levels (MD = −102.5 min per week) and increased daily hours of screen time (MD = 2.9 h per day); suggesting that restrictive mobility measures with the closure of schools and high schools had played an important role in these lifestyle behaviors worsening [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies published about healthy lifestyles during confinement have shown adverse collateral effects of the COVID-19 lockdown on physical health [ 1 ] in children and adolescents. It has been shown that U.S. children performed less physical activity and engaged in more sedentary behavior during the early COVID-19 period as compared to before the pandemic [ 2 ]. Another study in Spanish children and adolescents (3 to 16 years old) also reported a reduction in physical activity levels and increased both screen exposure and sleep time [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, strong evidence reveals that the majority of children and adolescents in many countries do not participate in sufficient physical activity (PA) [17]. Moreover, as observed among adults [18], adolescents' PA levels have been shown to decline during lockdown, probably because of the closure of schools, sports facilities, and public parks [19]. In this scenario, the promotion of PA participation among young people has represented a public health priority.…”
Section: Introductionmentioning
confidence: 99%